Development of a Novel Nanotextured Titanium Implant. An Experimental Study in Rats - Pelegrine, Andre Antonio; Moy, Peter Karyen; Moshaverinia, Alireza; Amaral Escada, Ana Lucia do [UNESP]; Calvo-Guirado, Jose Luis; Rosifini Alves Claro, Ana Paula [UNESP] (Mdpi, 2019)
This animal study evaluated the osseointegration level of a new nanotextured titanium surface produced by anodization. Ti-cp micro-implants (1.5 mm diameter by 2.5 mm in length) divided into two groups: titanium nanotextured surface treatment (Test Group) and acid etched surface treatment (Control Group). Surface characterization included morphology analysis using scanning electron microscopy and wettability by measuring contact angle. Sixteen Wistar rats were submitted to two micro implants surgical placement procedures. In each rat, one type of micro implant placed in each tibia. The animals sacrificed after two (T1) and six weeks (T2) post-implantation. After the euthanasia, tibias processed for histomorphometric analysis, which allowed the evaluation of bone to implant contact (BIC) and the bone area fraction occupancy between the threads (BAFO). Our surface analysis data showed that the Control Group exhibited an irregular and non-homogenous topography while the Test Group showed a nanotextured surface. The Test Group showed higher wettability (contact angle = 5.1 +/- 0.7 degrees) than the Control Group (contact angle = 75.5 +/- 4.6 degrees). Concerning the histomorphometric analysis results for T1, Control and Test groups showed BIC percentages of 41.3 +/- 15.2% and 63.1 +/- 8.7% (p < 0.05), respectively, and for BAFO, 28.7 +/- 13.7% and 54.8 +/- 7.5%, respectively (p < 0.05). For T2, the histomorphometric analysis for Control and Test groups showed BIC percentages of 51.2 +/- 11.4% and 64.8 +/- 7.4% (p < 0.05), respectively and for BAFO, 36.4 +/- 10.3% and 57.9 +/- 9.3% (p < 0.05), respectively. The findings of the current study confirmed that the novel nanotextured surface exhibited superior wettability, improved peri-implant bone formation, and expedited osseointegration.
Keywords: osseointegration; osteogenesis; titanium; dental implants